2018
DOI: 10.1002/ana.25247
|View full text |Cite
|
Sign up to set email alerts
|

Prodromal symptoms of multiple sclerosis in primary care

Abstract: Various clinical disturbances precede MS diagnosis by several years, supporting a prodromal phase to the disease and improving our clinical knowledge of early MS. Integrating these symptoms in the diagnostic procedure may help earlier disease identification. Ann Neurol 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
113
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 31 publications
12
113
5
Order By: Relevance
“…For example, neurologist or ophthalmologist/otolaryngologist encounters were similarly higher relative to controls, but did not differ when the two MS phenotypes were compared directly. Previous studies have reported the presence of a MS prodrome [2][3][4][5][6][7][8]. However, only one other study reported results by phenotype; Norwegian men aged 18-19 years entering military service exhibited cognitive deficits in the 2 years pre-onset of both RMS and PPMS, but possibly up to 20 years before PPMS onset [2].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, neurologist or ophthalmologist/otolaryngologist encounters were similarly higher relative to controls, but did not differ when the two MS phenotypes were compared directly. Previous studies have reported the presence of a MS prodrome [2][3][4][5][6][7][8]. However, only one other study reported results by phenotype; Norwegian men aged 18-19 years entering military service exhibited cognitive deficits in the 2 years pre-onset of both RMS and PPMS, but possibly up to 20 years before PPMS onset [2].…”
Section: Discussionmentioning
confidence: 97%
“…This period can include nonspecific symptoms before the 'classic' onset of disease. Previous studies have reported the presence of a MS prodrome [2][3][4][5][6][7][8] but have seldom considered the MS phenotypes. However, the phenotypes differ clinically [1,9]; recognition and diagnosis of PPMS are particularly challenging and subsequent therapeutic options are limited.…”
Section: Introductionmentioning
confidence: 99%
“…These results are of particular interest because a recent study has observed pwMS had significantly higher risk of presenting up to 10 years prior to a first demyelinating event with gastric, intestinal, urinary and anorectal disturbances, anxiety, depression, insomnia, fatigue, headache and various types of pain. (26) These autonomic symptoms that precede MS for up to 10 years are called MS prodrome and the more symptoms are present so is the risk of MS greater. If we put the results of the former study into the context with the autonomic MS prodrome, we may speculate that ANS is an important predictor of disease activity, even before the first demyelinating event.…”
Section: What Happens With Ad With the Progression Of Ms?mentioning
confidence: 99%
“…They enable the identification of risk factors many years prior to MS diagnosis . They have also been used to demonstrate an “MS prodrome” in the years preceding a clinical diagnosis of MS . Previous studies have not been able to study ethnicity across prospectively collected risk factors …”
mentioning
confidence: 99%